A new technique for assembling large-size GEM detectors. (26th June 2017) - You, W.; Zhou, Y.; Liu, J.; Shao, M.; Li, C.; Chen, H.; Tang, Z.; Sun, Y.; Zhang, Y.; Lv, Y.; Song, G.; Wang, X.; et al.
Abstract: An improved self-stretching technique is introduced to construct gaseous electron multiplier (GEM) chamber with size larger than 1 meter. This new assembly method, called as ``sliding self-stretching'', gives more uniform stretching force and better performance compared to its original version.